Interventions to reduce sedentary behavior and increase physical activity during productive work: a systematic review - Dianne ACM Commissaris; Maaike A Huysmans; Svend Erik Mathiassen; Divya Srinivasan; Lando LJ Koppes; Ingrid JM Hendriksen (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVE: This review addresses the effectiveness of workplace interventions that are implemented during productive work and are intended to change workers` SB and/or PA. METHODS: We searched Scopus for articles published from 1992 until 12 March 2015. Relevant studies were evaluated using the Quality Assessment Tool for Quantitative Studies and summarized in a best-evidence synthesis. Primary outcomes were SB and PA, both at work and overall (ie, during the whole day); work performance and health-related parameters were secondary outcomes. RESULTS: The review included 40 studies describing 41 interventions organized into three categories: alternative workstations (20), interventions promoting stair use (11), and personalized behavioral interventions (10). Alternative workstations were found to decrease overall SB (strong evidence; even for treadmills separately); interventions promoting stair use were found to increase PA at work while personalized behavioral interventions increased overall PA (both with moderate evidence). There was moderate evidence to show alternative workstations influenced neither hemodynamics nor cardiorespiratory fitness and personalized behavioral interventions did not influence anthropometric measures. Evidence was either insufficient or conflicting for intervention effects on work performance and lipid and metabolic profiles. CONCLUSIONS: Current evidence suggests that some of the reviewed workplace interventions that are compatible with productive work indeed have positive effects on SB or PA at work. In addition, some of the interventions were found to influence overall SB or PA positively. Putative long-term effects remain to be established.